Fate of Gold Nanoparticles in Laser Desorption/Ionization Mass Spectrometry: Toward the Imaging of Individual Nanoparticles - Prysiazhnyi, Vadym; Bednařík, Antonín; Žalud, Michal; Hegrová, Veronika; Neuman, Jan; Preisler, Jan (Journal of the American Society for Mass Spectrometry, 2023)
This study focuses on mapping the spatial distribution of Au nanoparticles (NPs) by laser desorption/ionization mass spectrometry imaging (LDI MSI). Laser interaction with NPs and associated phenomena, such as change of shape, melting, migration, and release of Au ions, are explored at the single particle level. Arrays of dried droplets containing low numbers of spatially segregated NPs were reproducibly prepared by automated drop-on-demand piezo-dispensing and analyzed by LDI MSI using an ultrahigh resolution orbital trapping instrument. To enhance the signal from NPs, an in source gas-phase chemical reaction of generated Au ions with xylene was employed. The developed technique allowed the detecting, chemical characterization, and mapping of the spatial distribution of Au NPs; the ion signals were detected from as low as ten 50 nm Au NPs on a pixel. Furthermore, the Au NP melting dynamics under laser irradiation was monitored by correlative atomic force microscopy (AFM) and scanning electron microscopy (SEM). AFM measurements of Au NPs before and after LDI MSI analysis revealed changes in NP shape from a sphere to a half-ellipsoid and total volume reduction of NPs down to 45% of their initial volume.